Local Value-Based Forest Resource Conservation Policies In Saradan, Madiun Regency (Social Forestry Policy) - Arief Budiono; Rizka Rizka; M Junaidi; Kiki Samudera; Aries Isnandar; Yogi Prasetyo (Syntax Corporation, 2022)
Forest conservation currently attracts the attention of numerous countries in the world, including Indonesia. This is because the world’s forests have experienced terrible damage, including due to deforestation. Principal policies are crucial to prevent the problem of forest deterioration. Thus, many countries apply policies with the paradigm of sustainable forest development. It is based on balancing the sustainability of the economic, ecologic, social, and cultural functions through non-centralistic forest resource management which values the society’s independence. In essence, this paradigm uses local wisdom as its basis. Some requirements must be fulfilled to reach the goals of the forest policies. One of them is society’s active participation in conserving the forests’ natural resources. Society's participation in environmental conservation is crucial, as they act as the determinants (subjects). Apart from that, they simultaneously experience the impact of the determined policies (object).